Religious Education and Vaccination: The Concept of Halal, From the Slippery Road to Herd Immunity - Wiryadinata, Halim (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This study aims to understand how religious education contributes to understanding vaccination to achieve herd immunity in society due to the COVID-19 pandemic. The diversity of understanding for vaccines and its ingredient creates an issue about halal and non–halal among Indonesian citizens. The dispersed understanding produces the swing opinions not to be vaccinated due to the understanding of the theological concept of Halal, and the final herd immunity is impossible to achieve. This core problem is triggered by two essential elements: culture and theological concepts. The present triggers, cultural and theological elements, invite the sociological method to access articles, journals, academic writing, and books to see the emic perspective of the problems. The sociological method evaluates and analyses the problems to get the possible answer to the research question. The result of this investigation is that vaccination is saving humanity from the destruction of the COVID-19 virus. It is also a theological blueprint of God's creation to use medical materials to stop the plague. The conclusion is drawn to state that vaccination is the knowledge of God's gift for humanity to end the pandemic of Covid-19. It is also a part of the social responsibility of religious people to open the door to vaccination places to convince the ingredient is the gift of the Creator through medical science.